Functional independence of persons with long-standing motor complete spinal cord injury in the Netherlands. (3rd May 2020) - Osterthun, Rutger; Tjalma, Tjitske A.; Spijkerman, Dorien C. M.; Faber, Willemijn X. M.; van Asbeck, Floris W. A.; Adriaansen, Jacinthe J. E.; Post, Marcel W. M.
Abstract : Context/Objective: Since life expectancy of persons with spinal cord injury (SCI) has improved, it is relevant to know whether this group is able to maintain functional abilities many years after onset of SCI. Objectives of this study were (1) to examine associations between time since injury (TSI) and functional independence in persons with long-standing SCI and (2) to explore associations between functional independence and level of injury, comorbidities, mental health, waist circumference and secondary health conditions (SHCs). Design: TSI-stratified cross-sectional study. Strata were 10–19, 20–29 and 30+ years. Setting: Community. Participants: 226 persons with long-standing SCI. Inclusion criteria: motor complete SCI; age at injury 18–35 years; TSI ≥ 10 years; current age 28–65 years; wheelchair dependency. Interventions: Not applicable. Outcome measures: The Spinal Cord Independence Measure III (SCIM) was administered by a trained research assistant. Level of injury, comorbidities, mental health, waist circumference and SHCs were assessed by a rehabilitation physician. Results: Mean TSI was 23.6 (SD 9.1) years. No significant differences in SCIM scores were found between TSI strata. SCIM scores were lower for persons with tetraplegia, autonomic dysreflexia, hypotension, more than four SHCs and a high waist circumference. In linear regression analyses, TSI nor age was associated with the SCIM total score. Only level of injury ( β  = –0.7; P < .001) and waist circumference ( β  = –0.1; P = .042) were independent determinants (explained variance 55%). Conclusion: We found no association between TSI and functional independence in persons with long-standing motor complete SCI. This study confirms the possible effect of overweight on functional independence.